Design, fabrication, and testing of trommel screening machine for fertilizer grading - Pandey, Shristi; Maharjan, Rendira; Gurung, Krisha; Dahal, Shreya; Pradhan, Rush; Lamichhane, Binaya Kumar (Journal of Innovations in Engineering Education, 2026)
Organic waste management and compost quality are rising concerns in developing nations like Nepal, where compost often lacks uniformity and standard grading. The grading process is usually performed manually, which is time-consuming, inconsistent, and inefficient. This research aimed to model, fabricate, and test a low-cost trommel screening machine that can separate compost based on particle size, ensuring higher quality and better application efficiency. The prototype was developed with locally available materials in the workshop of IOE Thapathali Campus and tested with compost obtained from community waste sites in Rikishi, Bhaktapur. A mean throughput of 90.09 ± 6.20 kg/h, a screening efficiency of 87.56 ± 4.56%, and an average energy cost of 0.0483 ± 0.0058 NRs/kg were shown by the fabricated model. The corresponding 95% confidence ranges were 83.58-96.59 kg/h, 82.77-92.34%, and 0.0422-0.0544 NRs/kg, respectively. The total fabrication cost of the machine was approximately NPR 45,000, significantly lower than commercially available systems. This study concludes that the machine provides a sustainable solution to improve compost quality at the community and municipal levels.